PERAN LEMBAGA PEMBIAYAAN SYARIAH DALAM MENDUKUNG KEMANDIRIAN EKONOMI MASYARAKAT DESA PAYAGELI KABUPATEN DELI SERDANG - Feby Salsabila Dasri; Nabila Nasywa; Nur Atikah; Muhammad Ikhsan Harahap (CV. Barokah Publsiher, 2025)
This study aims to analyze the role of Islamic bank financing institutions in supporting the economic independence of rural communities. Using a qualitative approach through interviews with local entrepreneurs, the study found that Islamic-based financing not only provides capital access but also builds responsibility, honesty, and blessings in economic activities. Islamic financial institutions play a strategic role in empowering rural MSMEs through profit-sharing and integrated financial education programs. The findings show that Islamic financing support increases local business productivity, enhances income, and strengthens sustainable rural economic independence.